Electronic model for superconductivity. - Essler, F; Korepin, V; Schoutens, K (1993)
We consider a model of strongly correlated electrons that exhibits superconductivity. It differs from the Hubbard model by nearest-neighbor interactions. We find the ground-state wave function (in one, two, or three dimensions) and show it to be superconducting for attractive and moderately repulsive on-site interaction. © 1993 The American Physical Society.